Discrimination of talcum powder and benzoyl peroxide in wheat flour by near-infrared hyperspectral imaging. (February 2020) - Fu, Xiaping; Chen, Jinchao; Fu, Feng; Wu, Chuanyu
Abstract : The presence of illegal additives in wheat flour is an important and broadly recognised global issue of food quality and safety. Hyperspectral imaging combines the advantages of spectroscopy and imaging techniques, and is widely used for food quality and safety evaluation. In this study, near-infrared hyperspectral imaging was used to discriminate low levels (<5.0%) of talcum powder and benzoyl peroxide (BPO) particles in wheat flour. After data pre-processing, spectra of wheat-talcum powder mixture samples were analysed by first derivative band difference, and the spectra of wheat-BPO mixture samples were analysed by spectral correlation measurement method and band ratio method. Successful results were obtained for discriminating single adulterants from wheat-talcum powder/BPO mixtures, as well as both adulterants synchronously from wheat-talcum powder-BPO mixtures. All these results show that NIR hyperspectral imaging technique combined with different spectral analysis methods can effectively discriminate the adulteration of talcum powder and BPO particles in wheat flour. Highlights: NIR hyperspectral imaging proved effective for adulterant discrimination. Talcum and BPO can be separately/synchronously discriminated in wheat flour. Spatial location of adulterants in wheat flour can be visualised in binary images. Particle size of adulterants affects the discrimination results.